Analysis of the Geometric Thinking Level of Primary School Students with Moderate Academic Ability in Mataram City: Evidence from a Plane Geometry Task - Radiusman Radiusman; Syarifuddin Syarifuddin; Lalu Sirajul Hadi; Prayogi Dwina Angga; Lalu Rafta Patech; Desinta Desinta (MASI Mandiri Edukasi, 2026)
Geometric thinking is a crucial skill for solving geometry problems and navigating everyday life. This descriptive qualitative study aims to analyze the levels of geometric thinking regarding plane figures among primary school students with moderate academic ability. The study also describes the errors students make when solving problems involving plane geometry. Data were collected through interviews and an analysis of students’ written answers to five open-ended questions designed to assess specific indicators of geometric thinking: 1) visual skills; 2) verbal skills; 3) drawing skills; 4) logical skills; and 5) applied skills. This study involved 531 fifth-grade students from 12 public primary schools in Mataram City; however, the analysis focused on 450 students classified as having moderate academic ability based on their obtained score intervals. The researchers interviewed five students who provided the most common answers for each question. The collected data were analyzed using thematic analysis, including familiarization, coding, searching for initial themes, reviewing and developing themes, defining and naming themes, and report writing. The results indicate that students with moderate academic ability demonstrated proficiency primarily in visual, drawing, and verbal skills, yet still frequently made errors regarding applied skills. The results also indicate that students with moderate mathematical ability have not yet fully grasped geometric concepts. These findings enable teachers to identify the capabilities and errors of students with moderate academic ability during geometry instruction, thereby improving their understanding of plane geometry.